Understanding parental stressors: An investigation of British tennis-parents - Harwood, C.; Knight, C. (Journal of Sports Sciences, 2009)
In this study, we examined the stressors experienced by British tennis-parents. The parents (n = 123) completed an extensive survey focused on the internal and external demands that they had encountered through having a child compete in the sport. The survey consisted of open-ended questions related to competition, coaching, organizational, personal, and developmental issues. Inductive and deductive content analysis resulted in the development of seven core themes of tennis-parental stressor: competition, coaches, finance, time, siblings, organization-related, and developmental. Parents experienced a diverse number of competitive stressors indicating the particular difficulties they faced before, during, and after matches involving their child, opponents, other parents, and officials. They also reported a wide range of organizational stressors that paralleled the financial, social, and personal investments that accompanied their support roles. The results of this research reinforce the importance of parents possessing the necessary skills to cope with the psychological, developmental, and logistical demands of competitive tennis. Implications with respect to induction workshops and education for coaches and parents are presented, as well as consideration for governing bodies to enhance their communication channels and logistical support. Future research recommendations are posed to build upon the study of this domain in youth sport.